Preliminary Result on Optimum Seed Generation Bandwidth for Object-Based Image Segmentation (OBIS) of Porphyritic Igneous Thin Sections - Nugroho, Rio Priandri; Widjaya, Victoria Vania Blanca; Roviansah, Mohamad (Pusat Survei Geologi, 2024)
Crystal size distribution (CSD) analysis is one of many methods for studying the crystallization history of magma. It involves labor-intensive digitation of all crystals, which may prolong the processing of large data sets. This study presents a preliminary result of Object-Based Image Segmentation (OBIS) as a semi-automatic approach in crystal digitation. Five data sets containing 9 photomicrographs of porphyritic igneous rock thin sections were processed using SAGA GIS. The procedure produced an optimum bandwidth equation of y = 38.455 ln(x) + 114, where x is the average size of sampled crystal in mm. Segmentation tests on another sample using the formula returned good and consistent results with important notes on sensitivity to textures which may result in crystal segment separation, such as fractures, veins, and sieve, as well as the inability to separate all groundmass crystals. Even though it shows good results, this formula only applies where the pixel-to-length conversion factor of 562.2 pixel/mm. Keywords: OBIS, SAGA GIS, Optimum bandwidth, Photomicrograph, Porphyritic igneous rock thin section.